3 In-Hospital Child Mortality after Consolidation of Two Pediatric Intensive Care Units - Parvez, Sehar (Paediatr Child Health, 2020)
BACKGROUND: While high-volume specialized Pediatric Intensive Care Units (PICUs) increase the survival of critically ill children, the benefits of consolidating PICUs to a single site may be outweighed by the need to transport critically ill children when the area serviced has a low population density and vast geography. OBJECTIVES: This study seeks to describe the impact of PICU consolidation on mortality of children from the southern part of a Canadian province, after presentation to nearest hospital, following consolidation of PICUs to a single more centrally located PICU. DESIGN/METHODS: We conducted a retrospective chart review of children with a primary residence in the southern part of the province, who died between January 2008 and December 2017 after presentation to the nearest hospital. Children who died prior to presentation to hospital or did not have return of spontaneous circulation at any time after presentation were excluded from analysis. Child demographics, year of death, cause of death, and Pediatric Risk of Mortality III (PRISM III) score, and duration and type of treatments provided were abstracted from health records. Population census data was obtained from the 2016 Canada Census. Deaths were grouped for analysis according to the child’s place of residence within three specific administrative areas. Nonparametric Mann Whitney U-test was used for descriptive analysis. RESULTS: Eighty-six (86) children from the southern part of the province died following presentation to the nearest hospital during the 10-year study period. The observed population rate of in-hospital deaths was 6.8 per 100,000 children per year before consolidation and 8.5 per 100,000 children per year after consolidation of PICU services. Variation in the population rate of in-hospital deaths before and after consolidation of PICUs was observed between administrative areas (p=0.016). The data did not appear to show an association with urban or non-urban areas. Children who died after consolidation were more likely to receive pain relief (p=0.013), and palliative care consultation (p=0.005) than those who died prior to consolidation. No change in acuity at presentation to hospital or cause of death was observed following PICU consolidation (p=0.3). CONCLUSION: This study did not find evidence of a change in the rate of in-hospital child deaths per 100,000 children following consolidation of PICU services in a Canadian province.